The Existence Of Ulama In The Digital Era: : A Framing Analysis Of Gus Miftah's Misspeaking Using Robert Entman's Model - Al-Masduqi, Himayatu Syarafatil Furqon; Matkur; Mustajab (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The advent of the digital era has profoundly reshaped the practice of Islamic preaching, allowing religious scholars (Ulama) to engage with broader and more diverse audiences through social media and other digital platforms. Yet, alongside this expanded reach comes a set of complex challenges, chief among them the heightened risk of verbal missteps, which can easily spark controversy, foster misinterpretation, and ultimately compromise the credibility of the Ulama in the public eye. This study seeks to explore the evolving role of the Ulama in the digital age, with particular emphasis on the challenges posed by verbal missteps and their implications for public perception. Utilizing a qualitative research design and content analysis methodology, the study investigates the cases of Gus Miftah and Herri Pras, two influential religious figures who encountered significant public backlash following communication errors on social media platforms. This analysis draws on Robert N. Entman's framing model to examine how media outlets and audiences construct and interpret the public statements of Ulama and how these interpretive frames shape their broader public image. The findings indicate that even minor verbal missteps can rapidly escalate into significant controversies, ultimately threatening to erode the public's trust in religious authority. Given these dynamics, the Ulama must cultivate digital literacy and adopt more deliberate, context-sensitive communication strategies. This study contributes original insights to the discourse on the communicative challenges confronting Ulama in the digital era, underscoring the critical need for their preparedness to navigate the complexities of social media to sustain their relevance and credibility as authoritative voices in Islamic scholarship.